Miguel Ángel de Marco, Sarmiento. Maestro de América. Constructor de la Nación, Buenos Aires, Emecé, 2016, 415 pp. - Eiris, Ariel Alberto (2017)
Fil: Eiris, Ariel Alberto. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina